Congruent and non-congruent pattern of postural preferences and preferred hand in an adolescent population - Dr. SUSIE JEYALYN DAVID; Dr. S. RAJASANKAR (International Journal of Pharma and Bio Sciences, 2017)
The establishment of motor system in humans track the basic principle of contralateral control of distal movements. At the anatomical level this concept is demonstrated in nearly complete crossing of corticospinal fibres which innervate distal muscles, including hand muscles. However, a particular quality of the human brain is that the two hemispheres are not symmetrical but are distinguished in a number of tasks, including the motor control of the two hands. Classical human right handedness is believed a behavioural manifestation of that specialization. We investigated the relationship between handedness, Congruent and Non-congruent pattern of arm folding and digital interlocking.